Leafhopper subfamily Ledrinae of the Indian subcontinent: 1. Description of Yelahanka gen. nov. (Hemiptera: Cicadellidae) with seven new species and new combinations - Viraktamath, C.a.; Webb, M. D.; Yeshwanth, H.m. (Zootaxa, 2021)
One new genus of the tribe Ledrini, Yelahanka gen. nov. is described with Petalocephala granulosa Distant as its type species. The genus is characterised by the flexing of the forewing laterad of a strongly carinate or keeled outer claval vein and the claval veins fused in the distal two thirds. Seven new species, Yelahanka canaraica sp. nov. (India: Karnataka), Y. kodaiensis sp. nov. (India: Tamil Nadu), Y. montana sp. nov. (India: Tamil Nadu), Y. nepalica sp. nov. (Nepal), Y. sikkimensis sp. nov. (India: Sikkim), Y. shillongensis sp. nov. (India: Meghalaya) and Y. trifida sp. nov. (India: Himachal Pradesh, Arunachal Pradesh) are described and illustrated. The following new combinations are proposed: Yelahanka bainbriggei (Distant) comb. nov., Y. granulosa (Distant) comb. nov., Y. punctata (Walker) comb. nov. and Y. tabulata (Distant) comb. nov.; originally punctata was placed in the genus Ledra Fabricius and remaining species were placed in Petalocephala Stål. Petalocephala bainbriggei Distant 1916 is treated as a junior synonym of Y. granulosa (Distant 1910) syn. nov. and P. tabulata Distant 1908 is treated as a junior synonym of Yelahanka punctata (Walker 1851) syn. nov. Y. granulosa is newly recorded from Africa (Tanzania and Kenya) and Malaya. Relationships of the new genus with other genera of Ledrini are discussed and a key to species of the genus is also provided.